2023
DOI: 10.2147/copd.s393323
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glucagon-Like Peptide-1 Receptor Agonists in Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is one of the common diseases of the respiratory system. As the disease recurs, damage to the airways and lung tissue gradually worsens, leading to a progressive decline in lung function, affecting the patient’s workforce and quality of life, and causing a huge social and economic burden. Diabetes is a common comorbidity of COPD and patients with COPD are at increased risk of developing diabetes, while hyperglycemia can also reduce lung function and contribute to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…GLP-1 as an incretin hormone possesses anti-inflammatory and immune-modulatory functions, and its receptor agonists contribute to decreased blood glucose levels [ 28 ]. Available studies have suggested that GLP-1 and its based agents have therapeutic potential in lung injury and COPD [ 29 , 30 ]. Wei et al have shown that GLP-1-based pharmaceuticals presented reduced occurrence in most chronic lung diseases, except for interstitial lung disease [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 as an incretin hormone possesses anti-inflammatory and immune-modulatory functions, and its receptor agonists contribute to decreased blood glucose levels [ 28 ]. Available studies have suggested that GLP-1 and its based agents have therapeutic potential in lung injury and COPD [ 29 , 30 ]. Wei et al have shown that GLP-1-based pharmaceuticals presented reduced occurrence in most chronic lung diseases, except for interstitial lung disease [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GLP-1RAs inhibit NLRP3 inflammasome both directly and indirectly. Shao et al ( Wang W. et al, 2023 ) found that GLP-1RAs mitigate liver damage caused by oxidative stress by promoting the mitophagy pathway and suppressing the NLRP3 inflammasome, an effect that can be eliminated by PINK1 siRNA.…”
Section: Molecular Mechanism Of Anti-as By Glp-1rasmentioning
confidence: 99%
“…GLP-1R reduces the inflammatory-induced response in the lungs, regulates oxidative stress and pulmonary function, and decreases excessive mucus production [47,48]. Furthermore, GLP-1R affects the mucosal membrane in the gastric tract by decreasing gastric secretions, which restrict gastric acid secretions and motility [49][50][51].…”
Section: Glucagon-like Peptide-1 Receptormentioning
confidence: 99%